Exploring the predictive potential of programmed death ligand 1 expression in healthy organs and lymph nodes as measured by 18F-BMS-986192 PET: pooled analysis of data from four solid tumor types - Tanja D de Gruijl; Rieneke van de Ven; Geke A P Hospers; Marc C Huisman; Gerben J C Zwezerijnen; C Willemien Menke-van der Houven van Oordt; Iris H C Miedema; Johanna E. E. Pouw; Anne Kwakman; Florentine E F Timmer; Adrianus J de Langen (Journal for ImmunoTherapy of Cancer, 2024)
Introduction Immune checkpoint inhibitors (ICIs) can elicit anticancer immune responses, but predictive biomarkers are needed. We measured programmed death ligand 1 (PD-L1) expression in organs and lymph nodes using 18F-BMS-986192 positron emission tomography (PET)-imaging and looked for correlations with response and immune-related adverse events.Methods Four 18F-BMS-986192 PET studies in patients with melanoma, lung, pancreatic and oral cancer, receiving ICI treatment, were combined. Imaging data (organ standardized uptake value (SUV)mean, lymph node SUVmax) and clinical data (response to treatment and incidence of immune-related adverse events) were extracted.Results Baseline PD-L1 uptake in the spleen was on average higher in non-responding patients than in responders (spleen SUVmean 16.1±4.4 vs 12.5±3.4, p=0.02). This effect was strongest in lung cancer, and not observed in oral cancer. In the oral cancer cohort, benign tumor-draining lymph nodes (TDLNs) had higher PD-L1 uptake (SUVmax 3.3 IQR 2.5-3.9) compared with non-TDLNs (SUVmax 1.8, IQR 1.4-2.8 p=0.04). Furthermore, in the same cohort non-responders showed an increase in PD-L1 uptake in benign TDLNs on-treatment with ICIs (+15%), while for responders the PD-L1 uptake decreased (−11%). PD-L1 uptake did not predict immune-related adverse events, though elevated thyroid uptake on-treatment correlated with pre-existing thyroid disease or toxicity.Conclusion PD-L1 PET uptake in the spleen is a potential negative predictor of response to ICIs. On-treatment with ICIs, PD-L1 uptake in benign TDLNs increases in non-responders, while it decreases in responders, potentially indicating a mechanism for resistance to ICIs in patients with oral cancer.